An anthropologic study on strategies for addressing health problems among the elderly in Bambuí, Minas Gerais State, Brazil Um estudo antropológico sobre as estratégias para resolver problemas de saúde entre idosos de Bambuí, Minas Gerais, Brasil - Elizabeth Uchôa; Josélia O. A. Firmo; Maria Fernanda Lima-Costa; Ellen Corin (Cadernos de Saúde Pública, 2011)
This paper explores the contribution of anthropological perspectives for clarifying the mechanisms through which socioeconomic circumstances influence the strategies developed by elderly for addressing their health problems in a small Brazilian city. Interviews with 20 key-informants explored the community's broad perception of the health situation of the elderly. Life histories collected from 30 elderly women examined their own perception of their health status and their health strategies. Narratives converge in emphasising the important role played by financial factors in accessing health services and medication. Life histories also describe some damaging strategies resorted to by the elderly to deal with their lack of resources. Elderly women emphasize the crucial support they receive from their family and/or neighbours to overcome health problems. Thus, the issue of poverty is not only a matter of socioeconomic circumstances, but also the poverty of broader social networks. Este artigo utiliza a abordagem antropológica para examinar mecanismos por meio dos quais a situação socioeconômica influencia as estratégias desenvolvidas por idosos residentes em uma pequena cidade brasileira para enfrentar seus problemas de saúde. Entrevistas com vinte informantes-chave visaram à percepção da comunidade acerca da saúde do idoso. Entrevistas com trinta senhoras idosas objetivaram a percepção que elas possuíam da saúde e estratégias adotadas para resolver tais problemas. As análises mostraram que as narrativas dos dois grupos convergem na ênfase do papel desempenhado por fatores financeiros no acesso aos serviços de saúde e aos medicamentos. As histórias de vida descreveram algumas estratégias prejudiciais à saúde para fazer frente à falta de recursos. As senhoras também destacaram a importância do apoio da família e/ou de vizinhos para superar problemas relacionados à saúde. Assim, a questão da pobreza não é só econômica, mas também a pobreza das redes sociais de apoio.